2019
DOI: 10.1177/0164027519877476
|View full text |Cite
|
Sign up to set email alerts
|

Improving Attitudes to Volunteering Among Older Adults: A Randomized Trial Approach

Abstract: Promoting engagement in formal volunteering represents a potential means of facilitating healthy aging. Given reluctance to participate in volunteering has been partially attributed to negative perceptions of various aspects of this activity, this study assessed whether trialing volunteering can improve perceptions among older people. Using a parallel-group design, Australians aged 60+ years ( n = 445) were randomly assigned to one of two conditions, one in which they were encouraged to trial volunteering and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…With the motivation of Understanding showing the highest values and the fact that a large proportion of the sample had university studies, we are dealing with people interested in growth and learning, contributions that they recognise their volunteering offers them, therefore generating beneficial feelings like in Faletehan et al ( 2020 ) or Ferreira et al ( 2012 , 2015 ). Likewise, as it is essentially a sample of retired people, as in Wilson and Musick ( 1997 ), the Enhancement function can be recognised to have a relevant role since, through their volunteering, they can feel involved and capable of contributing to society according to Russell et al ( 2019 ), Jongenelis et al ( 2020 ) and Wilding et al (2021). Along the same lines, it is logical that the Career function should appear last since they have mostly finished their professional careers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the motivation of Understanding showing the highest values and the fact that a large proportion of the sample had university studies, we are dealing with people interested in growth and learning, contributions that they recognise their volunteering offers them, therefore generating beneficial feelings like in Faletehan et al ( 2020 ) or Ferreira et al ( 2012 , 2015 ). Likewise, as it is essentially a sample of retired people, as in Wilson and Musick ( 1997 ), the Enhancement function can be recognised to have a relevant role since, through their volunteering, they can feel involved and capable of contributing to society according to Russell et al ( 2019 ), Jongenelis et al ( 2020 ) and Wilding et al (2021). Along the same lines, it is logical that the Career function should appear last since they have mostly finished their professional careers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the pleasant feelings of Compassion Satisfaction, and Engagement, other individual elements intercede in the causes whereby a person starts or carries on health and social care volunteering (Selli et al, 2008 ). Recent studies reported a positive association between older people's volunteering, cognitive functioning (Guiney et al, 2021 ; Han et al, 2020 ), physical health (Pettigrew et al, 2020 ) and acquisition of skills or increased social connectedness (Jongenelis et al, 2020 ; Russell et al, 2019 ; Wilding et al, 2021 ). Authors are according with Haski‐Leventhal's ( 2009 ) theoretical proposal based on altruistic motivations or civic concerns.…”
Section: Introductionmentioning
confidence: 99%